The Inefficacy of Naming Genocide in Contemporary Southeast Asia - Annie Elizabeth Pohlman (Humaniora, 2020)
This article examines two cases of ongoing persecution in Southeast Asia and the problems of naming either genocide. Specifically, I discuss the politics of naming the decades’ long persecution of the Rohingya in Burma and West Papuans genocide. Both cases highlight some critical points of contention within the field of genocide studies which revolve around competing conceptions of how and what genocides destroy. Often separated into liberal and post-liberal camps, or those which conceive of genocide as a crime or as a process, these competing views create deep divisions over what cases of mass violence can be named genocide, or not. I take up some of these highly politicized and moralistic debates around the naming of genocide in light of these two contemporary Southeast Asian cases; that of the Rohingya which arguably has been recognised as a case of genocide since the latest wave of violence in 2017; and the case of West Papua, which remains very much at the fringes of genocide studies. I also draw on the work of a range of scholars who question the “effectivity” of naming genocide. I argue that, in these two contemporary Southeast Asian cases, naming (Rohingya) and not-naming (West Papua) cases of ongoing persecution genocide has had little effect whatsoever.